AN AYURVEDIC MANAGEMENT OF SUBCLINICAL HYPOTHYROIDISM - A CASE REPORT - Jadhav, Dnyaneshwar Kantaram (International Journal of Research -GRANTHAALAYAH, 2018)
Ayurved is science of life. Its guide human being for living on preventive & curative both aspect. Its ancient knowledge which is still stand truth to time. There are many diseases which is not mentioned directly in Ayurveda texts is called as Anukta vikar. Subclinical hypothyroidism is one of such disease. Such disease specifically mentioned but its line of treatment described very well. The present case is 28 year old male patient was suffering from Bhaar vrudhi (weight gain) from last 2.5 years while symptoms like Drubalya (fatigue), Sheet prachiti (feeling excessive cold), Bhrama (vertigo), Shwasakashtata (dyspnoea after walking), Katishool (backache) since last 2 years. Patient on modern medicine still he doesn’t get any satisfy relief, at the end patient decide to take Ayurvedic treatment only. For treatment patient was came to Nakshatra Ayurved Panchkarma clinic & Research center, Mumbai. Ayurvedic management include internal medicine, Rukshaya bashpa peti sweda. After 1.5 month patient got Excellent Result. All symptoms disappear, weight reduces up-to 4 kg, TSH level comes from 7.71 to 3.23. This is single case study, will Collect data of more cases for further Research.